Dopamine D 1 Receptor Agonist PET Tracer Development: Assessment in Nonhuman Primates - Barret, Olivier; Zhang, Lei; Alagille, David; Constantinescu, Cristian C.; Sandiego, Christine; Papin, Caroline; Sullivan, Jenna M.; Morley, Thomas; Carroll, Vincent M.; Seibyl, John; Chen, Jianqing; Lee, Chewah; et al. (Journal of Nuclear Medicine, 2021)
Non-catechol-based high-affinity selective dopamine D receptor (D1R) agonists were recently described, and candidate PET ligands were selected on the basis of favorable properties. The objective of this study was to characterize in vivo in nonhuman primates 2 novel D1R agonist PET radiotracers, racemic F-MNI-800 and its more active atropisomeric (-)-enantiomer, F-MNI-968. Ten brain PET experiments were conducted with F-MNI-800 on 2 adult rhesus macaques and 2 adult cynomolgus macaques, and 8 brain PET experiments were conducted with F-MNI-968 on 2 adult rhesus macaques and 2 adult cynomolgus macaques. PET data were analyzed with both plasma-input-based methods and reference-region-based methods. Whole-body PET images were acquired with F-MNI-800 from 2 adult rhesus macaques for radiation dosimetry estimates. F-MNI-800 and F-MNI-968 exhibited regional uptake consistent with D1R distribution. Specificity and selectivity were demonstrated by dose-dependent blocking with the D antagonist SCH-23390. F-MNI-968 showed a 30% higher specific signal than F-MNI-800, with a nondisplaceable binding potential of approximately 0.3 in the cortex and approximately 1.1 in the striatum. Dosimetry radiation exposure was favorable, with an effective dose of about 0.023 mSv/MBq. F-MNI-968 has significant potential as a D1R agonist PET radiotracer, and further characterization in human subjects is warranted.